Pengaruh Tingkat Literasi Keuangan Syariah dan Persepsi Kemudahan Layanan Digital Terhadap Loyalitas Masyarakat Dusun Iburaja Menggunakan Tabungan BSI - Franola, Aprelya; Hakim, Luqman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digitalization in rural Islamic banking is still hindered by the digital divide and limited public cognitive understanding. This study aims to examine and analyze the partial and simultaneous effects of Sharia Financial Literacy and Perceived Ease of Digital Service on the loyalty of the Dusun Iburaja Community in using BSI Savings. A quantitative approach with a causal-associative design was applied. The population consisted of BSI customers in Dusun Iburaja, selected using the total sampling technique. Data were gathered through online questionnaires and evaluated using multiple linear regression analysis. The results show that partially, Sharia Financial Literacy has a positive and significant effect on customer loyalty and emerges as the most dominant predictor. The Perceived Ease of Digital Service variable also proves to have a positive and significant partial effect. Simultaneously, both independent variables significantly influence customer loyalty. The combination of these variables explains most of the variation in loyalty, while the remainder is influenced by factors outside the model. The study concludes that accelerating financial inclusion in rural areas requires a harmonious synergy between strengthening Sharia value education and simplifying digital platform operations to mitigate customers' psychological anxiety